Apomictic Malus plants exhibit abnormal pollen development - Liu, Dan-Dan; Wang, Da-Ru; Yang, Xuan-Yu; Zhao, Chang-Hui; Li, Shao-Hua; Sha, Guang-Li; Zhang, Rui-Fen; Ge, Hong-Juan; Tong, Xian-Song; You, Chun-Xiang (Frontiers in Plant Science, 2023)
Apomixis is the asexual formation of seed with maternal background, it has important potential applications for plant breeding by fixing the good traits and stabilizing the heterosis of a maternal parent in offspring. Since most major crops do not express natural apomixis, some species of Malus plants display apomictic reproductive development. In this study, four apomictic and two sexual Malus plants were used to identify the apomictic character. Transcriptome showed that plant hormone signal transduction was the main environmental impactor during apomictic reproductive development. Additionally, four apomictic Malus plants were all triploid and displayed no pollen or little pollen in the stamen, it was associated with apomictic percentage, tea crabapple with the highest apomixis percentage showed no pollen in the stamens. Furthermore, microscope mother cell failed to meiosis and leads to abnormal development of pollen in a high percentage of apomictic Malus plants. Meiotic-related genes were decreased in apomictic plants. Pollen abortion can be used as a marker for identifying apomictic reproductive resources in apples, which provides a simple method of identifying apomictic reproductive resources in apples.